EFEKTIVITAS PROGRAM SIARAN KONSELING DI RADIO TRIJAYA BAGI MASYARAKAT KOTA YOGYAKARTA - , Wiratri Anindhita, S.IP, Dr. Ir. Ageng Setiawan Herianto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The counselling broadcasting program of Trijaya station radio is designed purposes in helping listeners to understand alternative wayout to their daily problems. People for solving their daily-psycological problems. The research objectives are : (1) to understand the effectivity of councelling program to their active and passive listeners